On Dam-Break Flow Routing in Confluent Channels - Chen, Sihan; Li, Yingjin; Tian, Zhong; Fan, Qiang (International journal of environmental research and public health, 2019)
The flood propagation at a confluence of channels exhibits a unique routing pattern, while there are few studies on the routing of dam-break flow in confluent channels. In this study, we conducted physical experiments and a numerical simulation to investigate the influence of different confluence angles on the routing of a dam-break flood. Experiments were carried out in smooth, transparent, rectangular prismatic channels to study the dam-break flow under four different confluence angles. The flow velocity was measured using an image processing technique, and the surface flow field was effectively captured by synchronously recording the particle motion images. Based on the variation of the water level and flow discharge, as the confluence angle increased, the retardation and abatement effects on the flood increased. Specifically, the flood arrival time was delayed by approximately 0.91% to 21.18%, and the peak flood discharge was reduced by approximately 9.05% to 58.36%. Combined with the surface flow field at the confluence and in the downstream sections, as the confluence angle increased, the impact points at the confluence and in the downstream straight sections moved upward, and the impact range was reduced. Combined with the pressure variation pattern, the routing of dam-break flow in the confluent channels experienced a process of impact-reflection-return-attenuation.